2008
DOI: 10.1007/s00213-008-1330-5
|View full text |Cite
|
Sign up to set email alerts
|

A mu opioid receptor gene polymorphism (A118G) and naltrexone treatment response in adherent Korean alcohol-dependent patients

Abstract: These results demonstrating a higher therapeutic effect of naltrexone in Korean alcohol-dependent individuals with the Asp40 variant genotype than the Asn40 genotype are consistent with previous study results in individuals of European descent. This is the first study to examine the pharmacogenetics treatment response to naltrexone in non-European subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 47 publications
(54 reference statements)
2
62
1
1
Order By: Relevance
“…This is an important empirical and clinical question for two reasons. First, the minor Asp40 allele of the OPRM1 gene found to predict a more positive response to naltrexone in the human laboratory (Ray and Hutchison, 2007a) and in clinical trials (Anton et al, 2008;Kim et al, 2009;Oslin et al, 2003) is markedly more prevalent among individuals of Asian descent (Arias et al, 2006). Second, the vast majority of the pharmacogenetic studies completed to date have been in Caucasian samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an important empirical and clinical question for two reasons. First, the minor Asp40 allele of the OPRM1 gene found to predict a more positive response to naltrexone in the human laboratory (Ray and Hutchison, 2007a) and in clinical trials (Anton et al, 2008;Kim et al, 2009;Oslin et al, 2003) is markedly more prevalent among individuals of Asian descent (Arias et al, 2006). Second, the vast majority of the pharmacogenetic studies completed to date have been in Caucasian samples.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies have examined the moderating role of the OPRM1 Asn40Asp SNP in response to opioid blockade in individuals of Asian descent. One was a clinical trial of naltrexone in Korean alcohol-dependent patients who found a positive pharmacogenetic effect when restricting the analyses to individuals who were medication compliant (Kim et al, 2009). The other study compared HPA-axis activation in response to a naloxone challenge among Caucasians and individuals of Asian descent and found that the pharmacogenetic effect was populationspecific and was only observed in Caucasians (HernandezAvila et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the sole haplotype that was associated with naltrexone response was the one carrying the 118G allele. In a diff erent prospective study in 63 alcohol-dependent Korean patients treated with naltrexone 25mg/day for fi rst 3 days and 50mg/day for the remaining days ofa 12-week treatment, Kim and colleagues have found that patients with at least one 118G allele took signifi cantly longer time to relapse than 118AA homozygotes [39]. Th ese results highlight that the association of OPRM1 A118G polymorphism with naltrexone responseoutscales potential ethnic diff erences.…”
Section: Introductionmentioning
confidence: 99%
“…An association of variations in the kappa-opioid system with alcohol dependence has also been described (Xuei et al, 2006). The OPRM1 118G genotype may moderate the subjective and neuronal response of opioid antagonists on alcohol and alcohol cue reactivity (Ashenhurst et al, 2012;Setiawan et al, 2012;Schacht et al, 2013) and modify response to treatment with opioid antagonists such as naltrexone, although there are conflicting results (Oslin et al, 2003;McGeary et al, 2006;Gelernter et al, 2007;Anton et al, 2008Anton et al, , 2012Kim et al, 2009;Koller et al, 2012;Oroszi et al, 2009;Kranzler et al, 2013). A recent metaanalysis supported the role of the A118G polymorphism of the OPRM1 gene in moderating the effect of naltrexone in patients with alcohol dependence and treatment response (Chamorro et al, 2012).…”
Section: Nalmefene For Alcohol Dependence 679mentioning
confidence: 99%